Identifikasi Escherichia coli Penyebab Waterborne Disease pada Air Mimun Kemasan dan Air Mimunm Isi Ulang - Gusti Rizka Khairunnida; Hetti Rusmini; Esteria Maharyuni; Efrida Warganegara (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Abstract. Background : Refilled water drinking store and packaged water drinking often can be found in cities with a high demand of water by the community, whether it’s drinking water or for daily basis. Contaminated water if being consumed, will cause a disease. Purpose : To know contamination of Escherichia coli bacteria cause of waterborne disease on refilled drinking water and packaged drinking water in Kelurahan Kemiling Raya by filtering method and isolate and identified on differential selective media. Method : Descriptive research design with experimental qualitative approach. Sample of refilled drinking water sample and packaged water drinking are filtered with a membrane filter and incubated on differential selective media Chromogenic Coliform Agar to know whether there is a contamination of Escherichia coli cause of waterborne disease. Result : There are Escherichia coli bacteria cause waterborne disease colonies in refilled drinking water on sample X, Y, and Z with each having 2,4 x 102 cfu/100ml, 6,8 x 102 cfu/100ml and sample Z having categorized by TBUD because of too much colonies, but on sample W there isn’t any. On packaged drinking water sample A and B both have the same number of colonies Escherichia coli which 2,0 x 100 cfu/250ml. Conclusion : The number of Escherichia coli bacteria on refilled drinking water is greater than packaged drinking water. There isn’t any Escherichia coli bacteria cause of waterborne disease in refilled drinking water whom uses reserved osmosis technology.